HIDROLISIS ENZIMATIK MINYAK IKAN UNTUK PRODUKSI ASAM LEMAK OMEGA-3 MENGGUNAKAN LIPASE DARI Aspergillus niger [Enzymatic Hydrolysis of Fish Oil for Production of Omega-3 Fatty Acids Using Lipase Derived from Aspergillus niger] - Sapta - Raharja; Prayoga - Suryadarma; Teni - Oktavia (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
Fish oil is the source of important fatty-acid, especially polyunsaturated fatty acid (PUFA) omega-3, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). Lipase catalysis activity of Aspergillus niger is low when it is used in fish oil hydrolysis. The activity of the lipase can be increased by adding organic solvent such as hexane into the media. This research aimed to determine temperature, pH and amount of water which produce the highest degree of hydrolysis of fish oil in the presence of hexane. Correlation between the highest degree of hydrolysis and the amount of omega-3 fatty acid was also investigated. The variables used in this research were temperatures (25-65) oC, pH (5-9), and water addition (1-5) %v/v. The highest degree of enzymatic hydrolysis of fish oil in the media without hexane was 28.07 % that was reached at 45oC and pH 5. In the presence of hexane, the highest degree of hydrolysis was 75.12 % which was reached at 5% water addition, temperature 45oC, and pH 5. GC-MS analysis showed that omega-3 fatty acid content especially EPA and DHA increased along with increase in the degree of hydrolysis. Concentration of omega-3 fatty acid produced without hexane addition was 18.42 % with EPA amounted to 12,17% and DHA 0,86%. Meanwhile omega-3 fatty acid content in the presence of hexane reached 21.93 % with EPA amounted to 17.75 % and DHA 1.21 %.